4CPS-055 Antimicrobial stewardship programme in primary healthcare emergency department. (2nd March 2018) - March, P; Mora, R Madridejos; Sanz, R Tomás; Font, I Santsalvador; Muñoz, E Rubio; Dalmau, A Mercadal; Pastor, J Pardo; Pelluz, C Sangrador; Borge, S Gallardo; Capafons, S Redondo; Picó, J Nicolás
Abstract : Background: The inappropiate use of antibiotics is leading to the appearance of resistance that, along with the decline in the development of new antibacterials, makes some experts talk about a future post-antibiotic period. Approximately between 80% and 90% of antibiotics use occurs in outpatients. It is estimated that about half of the antibiotic prescriptions in outpatients are inappropriate due either to antibiòtic selection, dosage or duration. Purpose: The primary objective of the project is to measure the impact of a multimodal intervention on the use of antibiotics in the emergency department (ED) of a primary care area (PCA). Material and methods: Prospective study with intervention in ED of a PCA (population: 260, 517) from January to June 2017. Recorded variables: defined daily dose (DDD) of amoxicillin, amoxicillin/clavulanic, macrolides, quinolones and other antibiotics from January to June 2017. The information was extracted from patients' medical prescriptions. Intervention: 1) Emergency physicians a) Commitment: The programme was presented to the head of the ED medical service, emergency physicians and primary care centre directors, through face-to-face sessions. Poster reminders of the project were placed in medical consultations and the ED. b) Actions directed to improve the prescription of antibiotics: An antimicrobial stewardship guideline was designed with local antimicrobial recommendations. c) Audit and feedback: Information was provided to emergency physicians, with their antimicrobial consumption rate establishing a comparison between physicians and the ED average. d) Education and experience: Interactive clinical sessions were held on different pathologies included in the antimicrobial stewardship programme. 2) Patients Posters and educational brochures for waiting rooms and consultations were designed. Results: From January to June 2017 total antibiotic use was reduced by 14.4% DDD compared to the same period of 2016. A decrease in the main families of antibiotics was observed: 22.42% amoxicillin, 6.89% amoxicillin/clavulanic, 21.96% macrolides, 32.42% quinolones and 1.73% of other antibiotics. Conclusion: The strategy designed to improve the use of antibiotics in the ED of the PCA led to a decrease in antibiotic consumption. References and/or Acknowledgements: No acknowledgements No conflict of interest